Antioxidant Therapy Attenuates Deficient Bone Fracture Repair Associated with Binge Alcohol Exposure - Volkmer, Dustin L (2011)
OBJECTIVES: Alcohol consumption is a known risk factor for traumatic injuries of all types and has been shown to produce detrimental effects on bone metabolism. While the mechanisms responsible for these detrimental effects are not well characterized, oxidative stress from alcohol exposure appears to play a central role. This study was designed to examine the effect of a short-term binge alcohol consumption pattern on fracture repair and the effect of an antioxidant, N-acetylcysteine, on fracture healing following binge alcohol consumption. METHODS: One hundred forty-four (144) adult male Sprague Dawley rats underwent unilateral closed femur fracture after injection of either saline or alcohol to simulate a binge alcohol cycle. Animals in the antioxidant treatment group received daily N-acetylcysteine following fracture. Femurs were harvested at 1, 2, 4 and 6 weeks following injury and underwent biomechanical testing and histological analysis. RESULTS: Binge alcohol administration was associated with significant decreases in biomechanical strength at one and two-week time points with a trend toward decreased strength at four and six-week time points as well. Alcohol-treated animals had less cartilage component within the fracture callus and healed primarily by intramembranous ossification. Administration of N-acetylcysteine in alcohol-treated animals improved biomechanical strength to levels comparable to the control animals and was associated with increased endochondral ossification. CONCLUSIONS: Our results indicate that binge alcohol alters the quality of fracture healing following a traumatic injury and that concurrent administration of an antioxidant is able to reverse these effects.